Association between abdominal obesity and cognitive decline among Chinese middle-aged and older adults: a 10-year follow-up from CHARLS - Wu, Qiong; Zhu, Xu; Feng, Dan; Zhang, Ziyan; Wen, Can; Xia, Xinbin (Frontiers in Public Health, 2025)
IntroductionThe relationship between abdominal obesity and cognitive decline has controversial results, and the mediating effect of high-density lipoprotein cholesterol (HDL-C) between them remains uncertain. This study aims to explore the association between abdominal obesity and cognitive decline in middle-aged and older adults, including dose-response relationship and age differences, as well as the mediating effect of HDL-C.MethodsData were obtained from the China Health and Retirement Longitudinal Study (CHARLS), involving 3,807 participants aged 45 and above from 2010 to 2020. The TICS-10 was used to assess cognitive function, and the group-based trajectory model (GBTM) was used to explore the potential heterogeneity of cognitive changes. Abdominal obesity was measured by baseline waist circumference (WC) and a sequentially adjusted unordered multinomial logistic regression was used to investigate the association between abdominal obesity and cognitive decline in middle-aged and older adults. Restricted cubic spline (RCS) model was adopted to analyze the dose-response relationship between WC and risk of cognitive decline. HDL-C was used as a mediator to examine the potential causal chain between abdominal obesity and cognitive decline.ResultsAmong the 3,807 participants, a total of 1,631 individuals (42.84%) had abdominal obesity. The GBTM identified 3 cognitive function trajectories: rapid decline (11.0%), slow decline (41.1%) and stable groups (47.9%). After controlling for confounders, participants with abdominal obesity were less likely to experience rapid decline (OR: 0.67, 95%CI: 0.51–0.8) and slow decline (OR: 0.81, 95%CI: 0.69–0.95) of cognitive function, compared to those with normal WC. RCS analysis showed a decreased risk of cognitive decline with increasing WC. In the age subgroup analysis, the protective effect was significant only in the population aged 50 and above. HDL-C mediated 19.15% (P < 0.05) of the relationship between abdominal obesity and cognitive decline.ConclusionAbdominal obesity had a significant protective effect on cognitive decline in Chinese middle-aged and older adults, with HDL-C playing a mediating role in the relationship between abdominal obesity and cognitive decline.